Bridal Confession in At the Altar Rail - Henriono Nugroho (Universitas Sanata Dharma, 2014)
Stylistics is a linguistic analysis on literary and non-literary texts. This article is concerned with a systemic stylistic analysis of a poem in terms of Systemic Functional Linguistics and Verbal Art Semiotics. The article uses library research, qualitative data, documentary study, descriptive method and intrinsic-objective approach. The semantic analysis results in both automatized and foregrounded meanings. The automatized meaning produces lexical cohesion and in turn, produces subject matter. Meanwhile, the foregrounded meaning produces the literary meaning and in turn, it creates a theme. Finally, the analysis indicates that the subject matter is about the planning of a marriage, the literary meaning is about the confession of an experienced bride, and the theme is about bridal confession.Keyword: automatized meaning, foregrounded meaning, literary meaning.